Virtual Reality Education In Era 5.0 - Hendrik Legi; Yoel Giban; Prima Hermanugerah (Journal Research of Social Science, Economics, and Management, 2022)
Advances in technology and information that are increasingly fast must be accompanied by the current quality of education so that they are able to answer the challenges of the times and are also ready to compete in the international realm. Because in fact, rapid technological progress is not enough to build progress in a country without being accompanied by the quality of its human resources so that poverty and various other social problems are resolved. Therefore, researchers want to find out more about virtual reality education models in the 5.0 era. The purpose of this study is to determine the application of virtual reality models in the world of education as a form of adaptation from the 5.0 era. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation to 40 respondents at school X. The data obtained will be analyzed in depth, so that it is known that the results of the study show that the virtual reality model can improve students' understanding in learning with students' KKM scores. which was previously achieved by 25% of students to 90% of students who completed the KKM. In addition, learning is also more fun and has a superior human sense and focuses on the quality of human resources which is considered through the quality of the graduates of school X.